2020
DOI: 10.3390/toxics8040102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil Amendments on Heavy Metal Immobilization and Accumulation by Maize Grown in a Multiple-Metal-Contaminated Soil and Their Potential for Safe Crop Production

Abstract: Soil amendments have been proposed for immobilizing metallic contaminants, thus reducing their uptake by plants. For the safe production of crops in contaminated soil, there is a need to select suitable amendments that can mitigate heavy metal uptake and enhance crop yield. The present experiment compared the effects of three amendments, hydroxyapatite (HAP), organic manure (OM), and biochar (BC), on plant growth and heavy metal accumulation by maize in an acidic soil contaminated with Cd, Pb, and Zn, and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 65 publications
(87 reference statements)
3
29
1
1
Order By: Relevance
“…Results obtained regarding decreased heavy metal concentration due to organic fertilizers application are also in accordance with [ 4 ]. Our results are also corroborated by an earlier study [ 32 ] that reported immobilization of heavy metals with the application of organic manure. The permissible maximum limits reported by [ 24 ] of the trace metals is Cd 3, Co 65, Cr 100, Cu 50, Pb 300, Fe 21000, Mn 2000, and Zn 200 mg kg −1 deposited in soil.…”
Section: Resultssupporting
confidence: 92%
“…Results obtained regarding decreased heavy metal concentration due to organic fertilizers application are also in accordance with [ 4 ]. Our results are also corroborated by an earlier study [ 32 ] that reported immobilization of heavy metals with the application of organic manure. The permissible maximum limits reported by [ 24 ] of the trace metals is Cd 3, Co 65, Cr 100, Cu 50, Pb 300, Fe 21000, Mn 2000, and Zn 200 mg kg −1 deposited in soil.…”
Section: Resultssupporting
confidence: 92%
“…La influencia de los HMA en la absorción de metales de las plantas varía según las concentraciones de éstos (Zhang et al, 2015). Se pudo comprobar que los hongos micorrízicos redujeron la acumulación de Cd en los tallos de plantas de cacao, presumiblemente mediante el aumento de la retención del metal dentro de las raíces (Wang et al, 2020). Figura 6.…”
Section: Resultados Y Discusiónunclassified
“…The soil was sampled from the surface layer (0–20 cm) of an abandoned paddy field contaminated with Cd, Pb and Zn, which was described in our recent study [ 21 ]. The soil was passed through a 2 mm sieve and sterilized at 121 °C for 2 h and then air-dried for plant culture.…”
Section: Methodsmentioning
confidence: 99%